2013
DOI: 10.1007/s00508-013-0478-0
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance may contribute to vascular dysfunction in patients with chronic obstructive pulmonary disease

Abstract: Altered glucose metabolism may be associated with progression of endothelial dysfunction in patients with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Seventeen original studies used ultrasound-based FMD to determine endothelial function in patients with COPD ( Figure 1, Table 1 and 2) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. A total number of 1228 participants was evaluated: 724 patients with a spirometry-based diagnosis of COPD (71% men; mean age: 65±5 years; body mass index (BMI): 27±2 kg/m 2 ) and 504 controls (56% men; mean age: 62±8 years; BMI: 27±2 kg/m 2 ) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen original studies used ultrasound-based FMD to determine endothelial function in patients with COPD ( Figure 1, Table 1 and 2) [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38]. A total number of 1228 participants was evaluated: 724 patients with a spirometry-based diagnosis of COPD (71% men; mean age: 65±5 years; body mass index (BMI): 27±2 kg/m 2 ) and 504 controls (56% men; mean age: 62±8 years; BMI: 27±2 kg/m 2 ) ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…During this time FMD decreased and fasting blood glucose increased. FMD was significantly negatively correlated with fasting blood glucose suggesting that patients with worse glucose control also had worse endothelial function [129]. Interestingly, other studies have demonstrated that uncontrolled diabetes mellitus is also associated with worse lung function in COPD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Rho-kinase inhibitors have also improved NO release from endothelial cells in vitro suggesting that blocking this pathway may provide another means to improve endothelial dysfunction [137]. As FMD is associated with poor glucose control screening COPD patients for fasting blood glucose and controlling abnormal glucose levels might provide another method of improving endothelial function in these patients [129]. …”
Section: Introductionmentioning
confidence: 99%
“…Insulin stimulates mitochondrial protein synthesis, which is crucial for maintaining mitochondrial functional activity . Insulin resistance causes endothelial dysfunction and impaired vasodilation . This can slow the increase in microvascular blood flow in skeletal muscle in response to moderate exercise, contributing to exercise limitation .…”
Section: Discussionmentioning
confidence: 99%
“…18 Insulin resistance causes endothelial dysfunction and impaired vasodilation. 19 This can slow the increase in microvascular blood flow in skeletal muscle in response to moderate exercise, contributing to exercise limitation. 20 Early onset of peripheral neuropathy in people with insulin resistance could also contribute to skeletal muscle impairment.…”
Section: Significance Of the Findingsmentioning
confidence: 99%